Accessory pulmonary ligament? a case report of lingula-diaphragmatic attachment - Krishnasamy, Sivakumar; Kok, Justin Shao Loong; Ismanizan, Muhammad Afiq; Othman, Nur Samiha; Subramaniam, Shamala Devi; Razif Abas, Razif (Universiti Putra Malaysia Press, 2024)
This case report presents a groundbreaking discovery of a hitherto undocumented ligament connecting the lingula lobe of the left lung to the diaphragm. The study involved a routine dissection of an adult Asian cadaver during a respiratory module practical session. The cord-like structure, approximately 7 cm in length and 2 cm in diameter, showed ligamentous features and was firmly attached to the upper surface of the left diaphragm without any vascular connections. This finding holds potential clinical significance, particularly during anatomical resections of the lung, as the ligament may need to be freed in surgeries such as lingulectomy, left upper lobectomy, or left lower lobectomy. However, the ligament's relevance differs from the well-known inferior pulmonary ligament, which aids in accessing crucial lymph nodes during left lower lobectomy. The absence of vascular structures suggests a lack of mediastinal lymph nodes associated with this newly identified ligament. Further research is warranted to fully understand its clinical implications.